Writing Errors Analysis: Subject-Verb Agreement Made by EFL Students - Yuntika, Arudia Risti; Anggreni, Afrillia; Jamiluddin, Jamiluddin; Usman, Sriati (Journal of English Language and Education, 2025)
Writing is a crucial skill in language learning, yet numerous students still struggle with grammatical accuracy, particularly subject–verb agreement (SVA). Previous studies have exposed students’ errors in SVA but most of them focused on school-level learners, leaving limited research on undergraduate academic writing. Thus, this study aims to identify and analyze SVA errors in the academic writing of English Education students at Tadulako University. Utilizing a descriptive qualitative design, data were obtained from the background and discussion sections of ten undergraduate theses and analyzed through Dulay et al.’s (1982) Surface Strategy Taxonomy, which includes omission, addition, misformation, and misordering. The findings present that omission errors as the most frequent (10 cases), mostly involving the omission of auxiliary verbs be (is, are, was, were) and verb endings such as –s or –ing. Misformation errors (6 cases) appeared when students used incorrect verb forms, particularly in mismatching singular and plural agreement. Next, addition errors (4 cases) occurred when unnecessary auxiliaries or suffixes were inserted into sentences, creating redundancy. The last, misordering errors (1 case) reflected difficulties in arranging subject–verb structures according to English syntax. These results indicate that students’ main difficulties lie in maintaining auxiliaries and singular–plural concord, showing the influence of both interlingual and intralingual factors. Overall, these results emphasize the importance of needs-based grammar instruction and ongoing error analysis to enhance learners’ grammatical accuracy to produce a qualified academic writing